Perlindungan Hukum Terhadap Anak Sebagai Korban - Leasa, Elias Zadrach; Latupeirissa, Julianus Edwin; Tuhumury, Carolina; Nussy, Jennifer Ingelyne; Supusepa, Reimon (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: The resolution of acts of violence faced by children as perpetrators, witnesses, and victims if the criminal law is resolved is still inappropriate, considering that between the perpetrator and the victim as children so that different ways of solving the case are still needed.Purposes of Devotion: The purpose of this writing is to study more deeply related to problems related to previous research as a follow-up to the results of the research in order to provide legal education, especially related to solving crimes related to the Protection of Children as Victims carried out with a Restorative justice approach, as a model for solving cases. Method of Devotion: The methods of activities carried out in this socialization activity are Coordinating with the church, Preparing material or materials in the form of powerpoint material related to the problems studied in this PKM activity, Preparing a location to be used for PKM activities at Shiloh Church, joint discussions between participants and resource persons.Results of the Devotion: The result of this writing that is intended to be achieved is to realize legal protection for children by providing guarantees for the fulfillment of their rights without discriminatory treatment. Protection for children who are in conflict with the law in the juvenile criminal justice process at every stage starting from investigation, prosecution and court to children's correctional institutions has not been able to provide protection that can realize a sense of justice for children and even children's rights are often neglected. Children have been positioned as objects and tend to harm children. In children's cases, children are sometimes the perpetrators, victims and witnesses, so serious protection and handling is needed to anticipate this so that it does not have a wider impact and harm the child. The process of protecting children as perpetrators, witnesses and victims must be given attention in the handling process, namely that it must be handled by officials who truly understand children's problems.